Fintech and cryptocurrency - Naved, Mohd; Devi, V. Ajantha; Gupta, Aditya Kumar (John Wiley & Sons, Inc., 2023)
FINTECH and CRYPTOCURRENCY Dive into the world of fintech and cryptocurrency through the engaging perspectives of this diverse group of authors and uncover the intricate connections between technology, finance, and cryptocurrency that make this a must-have for anyone intrigued by the future of digital society. Digital currencies, decentralization of money, and the growth of new technologies like blockchain, the Internet of Things, and machine learning have produced new opportunities and difficulties for banking and finance, as well as users of these services in electronic commerce. New banking and finance technologies may improve operational efficiency, risk management, compliance, and client pleasure, but they can decrease barriers and introduce new concerns, such as cybersecurity risk. Cryptocurrencies with smart contracts for payments and trading, as well as AI systems with adaptive algorithms that allow picture and speech recognition, expert judgement, group categorization, and forecasting in a variety of fields, are instances of increased automation. Simultaneously, the potentials pose risks and raise regulatory concerns. The rise of blockchain technology and its widespread use have had a significant impact on the operation and management of digital systems. At the same time, researchers and practitioners have paid close attention to digital finance. Blockchain's first applications were limited to the production of digital currency, but it has now been expanded to include financial and commercial applications. Innovative digital finance has had a huge impact on business and society since it has been extensively adopted by businesses and consumers. As a result, the goal of this edited book is to expand and deepen our knowledge of the business possibilities of novel blockchain and digital financial applications.
Description based on online resource; title from digital title page (viewed on November 15, 2023)
Keywords: Internet -- Money; Internet; Monnaie